Garden leave in South Africa: Vodacom (PTY) Ltd v Motsa & another 2016 (3) SA 116 (LC) - Do Cabeco, Anneline De Sousa (My University, 2018)
Employers increasingly impart corporate knowledge to their employees to sustain and grow their businesses. As a result, employers have become more reliant on their employees to remain in their employ. This augmented reliance on human capital has inflamed employers’ need for more strenuous control of employee mobility. Employers resultantly look to legal mechanisms to restrict employees who defect from imparting invaluable confidential information and trade secrets to new employers, who are often competitors. Garden leave is one such legal mechanism. Garden leave is aimed at sterilising defecting employees of their corporate knowledge in order to prevent such defecting employee from divulging such knowledge to a new employer. This is usually achieved by removing the defecting employee from the workplace for the duration of the garden leave period. Although the employee continues to receive remuneration during the garden leave period, it has a negative impact on the defecting employee, particularly with regards to his inability to work and exercise his skills during this period. Internationally, in jurisdictions such as the United Kingdom and New Zealand, garden leave provisions have become a common feature of employment contracts, particularly those of senior employees. In South Africa, provisions on garden leave has also found its way into employment contracts, as is evident from the Vodacom (Pty) Ltd v Motsa & another 2016 (3) SA 116 (LC) case. The Vodacom judgment is the first South African judgment dealing with garden leave. There is currently no other jurisprudence or legislation in South Africa relating to the principles of garden leave. This paper intends to illustrate the desperate need in South Africa for judicial and/or legislative direction with regards to garden leave. In doing so, this paper aims to critically analyse the Vodacom judgment. Within this critical analysis, this paper will investigate the principle of garden leave as established in the United Kingdom and New Zealand respectively. This paper will conclude with recommendations on how South African courts, in future, should use the principles from these jurisdictions as a way forward in overseeing garden leave in South Africa.
Submitted in partial fulfilment of the requirements for the degree of Master of Laws by Coursework and Research Report at the University of Witwatersrand, Johannesburg, 2018
Keywords: Law--South Africa; Law--South Africa; Legislation--South Africa